Association of the c.385C>A (p.Pro129Thr) polymorphism of the fatty acid amide hydrolase gene with anorexia nervosa in the Japanese population. Issue 4 (24th February 2014) - Ando, Tetsuya; Tamura, Naho; Mera, Takashi; Morita, Chihiro; Takei, Michiko; Nakamoto, Chiemi; Koide, Masanori; Hotta, Mari; Naruo, Tetsuro; Kawai, Keisuke; Nakahara, Toshihiro; Yamaguchi, Chikara; et al.
Abstract The functional c.385C>A single‐nucleotide polymorphism (SNP) in the fatty acid amide hydrolase (FAAH) gene, one of the major degrading enzymes of endocannabinoids, is reportedly associated with anorexia nervosa (AN). We genotyped the c.385C>A SNP (rs324420) in 762 lifetime AN and 605 control participants in Japan. There were significant differences in the genotype and allele frequencies of c.385C>A between the AN and control groups. The minor 385A allele was less frequent in the AN participants than in the controls (allele‐wise, odds ratio = 0.799, 95% confidence interval [CI] 0.653–0.976, P = 0.028). When the cases were subdivided into lifetime restricting subtype AN and AN with a history of binge eating or purging, only the restricting AN group exhibited a significant association (allele‐wise, odds ratio = 0.717, 95% CI 0.557–0.922, P = 0.0094). Our results suggest that having the minor 385A allele of the FAAH gene may be protective against AN, especially restricting AN. This finding supports the possible role of the endocannabinoid system in susceptibility to AN.